Perceived Usage of Smart Phone for Academic Activities by the Undergraduate Science Education Students of the Federal University of Kashere, Gombe State - Umar, Sani Alhaji; Ibrahim, Ahmed; Danyo, Kunata; Abdullahi, Rabiu; Adam, Maryam Umar (Kashere Journal of Education, 2025)
This study examines perceived usage of smartphones for academic activities by the undergraduate science education students of the Federal University of Kashere, Gombe State. Four (4) objectives and four (4) research questions were raised. The study adopted a descriptive research design using a population of 419 undergraduate science education 400 level students in federal university of Kashere, Gombe State. The sample size of the study was 200 students, which is determined using Krejcie and Morgan’s (1970) table. The researcher used proportionate sampling techniques to determine the proportion of students in each discipline. Then a simple random sampling technique was used for the study to select the sample of the study. A structured questionnaire was adapted, titled ‘Perceived Usage of Smartphone Questionnaire’ (PUSQ), developed by the researcher. Split half method was used to establish the reliability of the instrument. Two experts in science education validated the instrument to ensure its content and face validity. The questionnaire was tested for reliability on twenty (20) randomly selected students from science education federal university of Kashere, who are not part of the study. The data gathered from the pilot study was analysed ` to check for internal consistency of reliability and the spearman brown formula was used to get the reliability index of 0.85. The data collected were analysed using mean and standard deviation, among others. The findings showed that undergraduate science education students are aware of the usage of smartphones for academic activities. It was revealed all the respondents agreed the usage of smartphones has a positive and negative impact on their school activities among undergraduate science. It was therefore recommended that Mobile learning should be incorporated into the school curriculum and be taught at various levels to enhance better knowledge on how to make use of smartphones for academic purposes. In the future, research must be done to find out the impact of smartphones on the brain or human head, in the sense of whether they cause any biological effects on the human head or brain leading to the addiction students are having to them.